(untitled) (International Journal of Nursing Education, 2020)
Objects: To determine correlations among age, parity, and contraception using pap smear results. Method: The study was a correlative descriptive. The independent variables are age, parity, and contraception using, while the dependent variable the result of pap smear examination. The samples were 60 respondents. Data were collected using a questionnaire and analysis using the Chi-Square test at an error rate of 0.05. Results: There was no significant correlation between age and the result of a pap smear examination (p>0.734). There was no significant correlation between parity and the result of a pap smear examination (p>0.204). There was a correlation between contraception using and the results of pap smear examination p<0.004. Conclusion: It is expected that health workers can improve education and health promotion about cervical cancer prevention by holding seminars or examinations of cervical cancer detection by doing pap smears, and women who have done pap smears with normal results can have repeat pap smears a year later, and abnormal pap smears can repeat. Pap smear again performed 6 months after the previous pap smear.